The Ethno-STEM Project Based Learning Model in Fostering Prospective Teachers’ Creativity in Designing Science Learning Media and Modules for Primary Schools - Suranti, Ni Made Yeni; Astria, Fitri Puji; Rahmatih, Aisa Nikmah; Alimuddin, Nurkhaerat (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Creativity is a crucial ability in teacher education, especially for prospective teachers, as it relates to designing innovative, engaging, and contextually relevant learning strategies, methods, and media. However, the creativity of prospective teachers in designing primary science learning remains a challenge, as teaching practices are often conventional and less connected to local cultural contexts. This study aims to examine the effectiveness of the Ethno-STEM Project Based Learning (PjBL) model in fostering prospective teachers’ creativity in designing science learning media and modules for primary schools. The research was conducted at a University in Mataram involving 59 students of the Elementary School Teacher Education study program, divided into two classes. Data were collected using product assessment observation sheets with a Likert-scale questionnaire (1–4), and the scores were analyzed descriptively to determine the level of creativity demonstrated in the students’ products. The results show that students successfully developed learning products in the form of media and modules integrated with Ethno-STEM. Based on 15 indicators, the average score for learning media was 81.69, while the average score for modules was 82.52. These findings indicate that the products were in the good category, reflecting a positive impact of the model on fostering prospective teachers’ creativity.